The aryl hydrocarbon receptor in tumor immunity - Platten, Michael; Litzenburger, Ulrike; Wick, Wolfgang (OncoImmunology, 2012)
The aryl hydrocarbon receptor (AHR) binds environmental toxins and mediates immune regulation. The tryptophan metabolite kynurenine has now been identified as an endogenous ligand of the human AHR constitutively produced by gliomas and other types of cancer via tryptophan-2,3-dioxygenase (TDO), thereby suppressing antitumor immune responses via the AHR. Thus, this pathway represents an important novel target for cancer immunotherapy.